Correction: TAZ Expression as a Prognostic Indicator in Colorectal Cancer. - Hiu-Fung Yuen; Cian M McCrudden; Yu-Han Huang; Jill M Tham; Xiaoqian Zhang; Qi Zeng; Shu-Dong Zhang; WanJin Hong (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0054211.].